8α-Hydroxypinoresinol isolated from Nardostachys jatamansi ameliorates cerulein-induced acute pancreatitis through inhibition of NF-κB activation. (October 2019) - Choi, Ji-Won; Shin, Joon Yeon; Jo, Il-Joo; Kim, Dong-Gu; Song, Ho-Joon; Yoon, Chi-Su; Oh, Hyuncheol; Kim, Youn-Chul; Bae, Gi-Sang; Park, Sung-Joo
Highlights: HP inhibited cerulein-induced acute pancreatitis. HP inhibited activation of the NF-κB signaling pathways in acute pancreatitis. HP exerts anti-inflammatory effects on acute pancreatitis. Abstract: Acute pancreatitis (AP) is a severe inflammatory condition of the pancreas, with no specific treatment available. We have previously reported that Nardostachys jatamansi (NJ) ameliorates cerulein-induced AP. However, the specific compound responsible for this inhibitory effect has not been identified. Therefore, in the present study, we focused on a single compound, 8α-hydroxypinoresinol (HP), from NJ. The aim of this study was to determine the effect of HP on the development of pancreatitis in mice and to explore the underlying mechanism(s). AP was induced by the injection of cerulein (50 μg/kg/h) for 6 h. HP (0.5, 5 or 10 mg/kg, i.p.) was administered 1 h prior to and 1, 3 or 5 h after the first cerulein injection, with vehicle- and DMSO-treated groups as controls. Blood samples were collected to determine serum levels of amylase, lipase, and cytokines. The pancreas was removed for morphological examination, myeloperoxidase (MPO) assays, cytokine assays, and assessment of nuclear factor (NF)-κB activation. The lungs were removed for morphological examination and MPO assays. Administration of HP dramatically improved pancreatic damage and pancreatitis-associated lung damage and also reduced amylase and lipase activities in serum. Moreover, administration of HP reduced the production of pro-inflammatory cytokines, such as tumor necrosis factor (TNF)-α, interleukin (IL)-1β, and IL-6 in the pancreas and serum during AP. In addition, the administration of HP inhibited degradation of inhibitory κ-Bα (Iκ-Bα), NF-κB p65 translocation into nucleus and NF-κB binding activity in the pancreas. Our results suggest that HP exerted therapeutic effects on pancreatitis and these beneficial effects may be due to the inhibition of NF-κB activation.